A whirlwind vacation - Krulik, Nancy E. (New York : Grosset & Dunlap, 2005)
Katie is very excited about her family's trip to London, Paris, Madrid, and Venice, but when the magic wind strikes not once, but four times, Katie's European vacation is turned upside down.
Keywords: Vacations -- Juvenile fiction